Massachusetts Youth Screening Instrument-2 (MAYSI-2): relationships with the Posttraumatic Stress Disorder Checklist - Civilian Version (modified version) : among youth from the community and detention facilities - Campos, Telma Renata Latães (2014)
Dissertação de mestrado em Psicologia Clínica e Saúde (Psicologia Forense), apresentada à Faculdade de Psicologia e de Ciências da Educação da Universidade de Coimbra